Bioclimate influence on seed germination and seedling morphology parameters in Pterocarpus erinaceus Poir., 1804 (Fabaceae) - Adji, Beda Innocent; Akaffou, Doffou Sélastique; Kouassi, Kouadio Henri; Houphouet, Yao Patrice; Duminil, Jerôme; Sabatier, Sylvie Annabel (International Journal of Environment, Agriculture and Biotechnology, 2021)
Pterocarpus erinaceus is over-exploited for its multiple uses. Its exploitation and trade are strictly prohibited in many countries, including Côte d'Ivoire, to prevent its extinction. It is nevertheless imperative to restore populations of this species, while accounting for its germinative capacities and its adaptation to changing climates. The aim of this study was to assess the seed germination and seedling development in Pterocarpus erinaceus in three different environments. A total of 2,160 seeds from different seed trees and 540 individuals germinated from seeds were selected and evaluated. The trials were conducted at three sites with distinct microclimates (two nurseries in Côte d’Ivoire and one greenhouse in France). The results showed that the environment had a significant influence on germination parameters (P < 0.05), whereas the seed trees did not (P > 0.05). The environment influenced the height and internodes length of the seedlings (P < 0.05). However, the diameter, number of leaves, and the length and width of the leaves of the seedlings were statistically identical from one site to another (P > 0.05). Seed trees influenced the number and length of seedlings leaves (P<0.05). PCA showed that the seedlings developed better in the Montpellier greenhouse and at the Daloa site than Korhogo site. This information could guide the choice of ideal environments for the implementation of reforestation or agroforestry programs based on Pterocarpus erinaceus in the current context of climate change from a nursery. This study could be extended to other species in order to regenerate important species in disturbed ecosystems.